2020
DOI: 10.1094/phyto-01-20-0020-r
|View full text |Cite
|
Sign up to set email alerts
|

Sources, Spectrum, Genetics, and Inheritance ofPhaseolus vulgarisResistance AgainstXanthomonas citripv.fuscans

Abstract: Common bean (Phaseolus vulgaris) is one of the most consumed agricultural products in the world. Its production is affected by common bacterial blight (CBB) caused by Xanthomonas citri pv. fuscans and X. phaseoli pv. phaseoli. In this work, we investigated the spectrum, genetics, and inheritance of common bean resistance to X. citri pv. fuscans. Inoculation of nine selected cultivars with an X. citri pv. fuscans strain showed that BRS Radiante and IAPAR 16 were resistant. These two cultivars were also resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…The common bean cultivars tested here showed different levels of resistance to Xcf, indicating that it is of quantitative type, which is consistent with results of previous reports for CBB (Monteiro et al, 2020; Paiva et al, 2018; Singh & Muñoz, 1999; Yu et al, 2012). Moreover, the AUDPC estimates varied from 19 to 55, a range that is similar to that reported by Durham (2011), who found a maximum value of 59.9 in a similar study using Xpp strains.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The common bean cultivars tested here showed different levels of resistance to Xcf, indicating that it is of quantitative type, which is consistent with results of previous reports for CBB (Monteiro et al, 2020; Paiva et al, 2018; Singh & Muñoz, 1999; Yu et al, 2012). Moreover, the AUDPC estimates varied from 19 to 55, a range that is similar to that reported by Durham (2011), who found a maximum value of 59.9 in a similar study using Xpp strains.…”
Section: Discussionsupporting
confidence: 92%
“…So far, the vast majority of studies have investigated common bean resistance against Xpp and only a few have addressed resistance to Xcf (Monteiro et al, 2020; Mutlu et al, 2008; Paiva et al, 2018). Nonetheless, it has been shown that some components of plant resistance are more effective against one of the bacterial pathogens, either Xpp or Xcf (Mutlu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Different Xpp-Xcf strains may have different levels of pathogenicity regardless of whether they belong to one or the other pathovars (Mkandawire et al, 2004). In addition, common bean resistance to CBB is mediated by numerous quantitative trait loci (Monteiro et al, 2020;Singh and Miklas, 2015;Yu et al, 2012). Differences in aggressiveness combined with the presence of quantitative resistances lead to a wide range of possible disease intensities (Duncan et al, 2011).…”
Section: Introductionmentioning
confidence: 99%